2006
DOI: 10.1073/pnas.0606212103
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of dynamin completely blocks compensatory synaptic vesicle endocytosis

Abstract: The ability of synapses to sustain signal propagation relies on rapid recycling of transmitter-containing presynaptic vesicles. Clathrinand dynamin-mediated retrieval of vesicular membrane has an undisputed role in synaptic vesicle recycling. There is also evidence for other modes of vesicle retrieval, including bulk retrieval and the so-called kiss-and-run recycling. Whether dynamin in required for these other modes of synaptic vesicle endocytosis remains unclear. Here, we have tested the role of dynamin in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
195
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(220 citation statements)
references
References 51 publications
(85 reference statements)
24
195
0
1
Order By: Relevance
“…Therefore, to identify isoformand/or splice-variant-specific functions of dynamin, it would be necessary to perform isoform-specific knockout and reconstitution experiments. In support of this approach, it was recently shown (Ferguson et al, 2007) that Dyn1 KO synapses exhibited a less severe phenotype than obtained with dominant-negative dynamin mutants, such as shibire (Koenig and Ikeda, 1989) or with the dynamin inhibitor, dynasore (Newton et al, 2006). These authors also provided evidence for isoform-specific function at the synapse because reexpression of either Dyn1 or Dyn3, but only to a lesser degree by Dyn2, could rescue the defect in Dyn1 KO neurons (Ferguson et al, 2007).…”
supporting
confidence: 50%
“…Therefore, to identify isoformand/or splice-variant-specific functions of dynamin, it would be necessary to perform isoform-specific knockout and reconstitution experiments. In support of this approach, it was recently shown (Ferguson et al, 2007) that Dyn1 KO synapses exhibited a less severe phenotype than obtained with dominant-negative dynamin mutants, such as shibire (Koenig and Ikeda, 1989) or with the dynamin inhibitor, dynasore (Newton et al, 2006). These authors also provided evidence for isoform-specific function at the synapse because reexpression of either Dyn1 or Dyn3, but only to a lesser degree by Dyn2, could rescue the defect in Dyn1 KO neurons (Ferguson et al, 2007).…”
supporting
confidence: 50%
“…Our findings suggest that dynamin could be recruited to the neck of closing clathrin-coated pits when their curvature is sufficiently high, and that its polymerization further constricts them to 10 nm. In vivo, dynamin appears at the clathrin-coated pits at the end of their formation (11)(12)(13), when the neck has a radius of ∼20 nm (35), close to the value of the critical radius (19 nm) we found for dynamin at 440 nM. Giant Unilamellar Vesicles.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, a potent and highly specific non-competitive inhibitor of dynamin GTPase activity was identified that blocks dynamin-dependent endocytosis in cells (30,31). We tested the ability of this inhibitor, termed dynasore, to prevent the internalization of LRP1.…”
Section: Pdgf-mediated Tyrosine Phosphorylation Of Lrp1 Does Not Occumentioning
confidence: 99%